Effect of type of feed, stocking density and grow-out site on gonad index, growth and survivorship of cultured sea urchin (Tripneustesgratilla) - Juinio-Meñez, Marie Antonette; Bangi, Helen Grace P.; Malay, Maria Celia D. (2008)
Grow-out culture of sea urchins in sea cages was developed as a means to enhance the recovery ofdepleted natural populations and to provide a supplemental source of income for fisherfolk. To improvereproductive output and commercial value of hatchery-produced sea urchins, the effects of food type,stocking density and grow-out site on test diameter (TD) growth, survivorship and gonad index (GI)were determined. Sea urchins fed with Sargassum spp. had higher TD growth rates, GI and bettergonad color than those fed with seagrass (Thalassia hemprichii). No significant differences werefound in the average growth rates of Sargassum-fed sea urchins reared at low and high stockingdensity. However, survivorship and average GI were significantly higher in lower stocking densitycages (200–250 sea urchins per m2). Reduction of density in the cages before harvest increased GIsignificantly. Survivorship in the sea cages was high in all grow-out sites except during the secondexperiment where mass mortalities occurred due to low salinities. Grow-out site and period hadsignificant effects on GI but not on TD growth. Possible effects of environmental and temporal factors,and implications of the results on the resource management and culture of sea urchins are discussed.
Keywords: Sea urchins